Common statistical errors even YOU can find. Part 2: errors in multivariate analyses and in interpreting differences between groups. - Lang T (AMWA Journal: American Medical Writers Association Journal, 2003)
This article is the second in a series in which I describe several of the more common statistical errors in the biomedical literature. The first article in the series focused on 10 errors in descriptive statistics and in interpreting probability, or P values. Here, I provide an overview of multivariate analyses (regression analysis and analysis of variance, or ANOVA) and describe nine errors in interpreting differences between groups.